Adult height in girls with idiopathic central precocious puberty treated with triptorelin - Corripio, Raquel; Soriano-Guillén, Leandro; Herrero, Francisco-Javier; Castro-Feijoó, Lidia; Escribano, Aránzazu; Sol-Ventura, Paula; Espino, Rafael; Vela, Amaia; Labarta, José-Ignacio; , The Spanish PUBERE Group; Argente, Jesús; Díez López, Ignacio; et al. (Frontiers in Endocrinology, 2024)
Objective: Idiopathic central precocious puberty (CPP) precipitates epiphyseal fusion of growth plates in long bones, leading to reduced adult stature. Gonadotropin-releasing hormone analogues (GnRHa) are the treatment of choice for idiopathic CPP, but their benefit on height gain is unclear. We aimed to elucidate the effects of GnRHa treatment on adult height in girls with idiopathic CPP. Design: This prospective observational descriptive study analyzed data of girls with idiopathic CPP diagnosed at 55 centers in Spain between January 1, 1998 and December 31, 2012 included in the Spanish Society for Pediatric Endocrinology’s national registry. Methods: We included girls with idiopathic CPP (thelarche < 8 years, positive LHRH stimulation test, bone age > 1 year older than chronological age, and normal brain imaging) treated with triptorelin (3.75 mg monthly, adjusted according to LHRH test results and clinical findings). We assessed weight, height, BMI, and secondary sexual characteristics every 6 months and bone age every 12 months until adult height (AH) was attained. The primary outcome was the difference between AH and target height (TH). Results: A total of 465 girls (18.90% adopted) were included; we analyzed data recorded at treatment end in 358 girls and at AH in 216. Mean difference between AH and TH was -1.5 (95%CI: -2.56‒ -0.45) cm and between AH and PAH 2,57 (95%CI:-3.56‒ -1.58) cm. Conclusions: GnRHa treatment helps preserve genetic growth potential in girls with idiopathic CPP.